Factor XIII-guided treatment algorithm reduces blood transfusion in burn surgery - João Miguel Gonçalves Valadares de Morais Carneiro; Joana Alves; Patrícia Conde; Fátima Xambre; Emanuel Almeida; Céline Marques; Mariana Luís; Ana Maria Mano Garção Godinho; Fernando Fernandez-Llimos (Revista Brasileira de Anestesiologia)
Abstract Background and objectives: Major burn surgery causes large hemorrhage and coagulation dysfunction. Treatment algorithms guided by ROTEM® and factor VIIa reduce the need for blood products, but there is no evidence regarding factor XIII. Factor XIII deficiency changes clot stability and decreases wound healing. This study evaluates the efficacy and safety of factor XIII correction and its repercussion on transfusion requirements in burn surgery. Methods: Randomized retrospective study with 40 patients undergoing surgery at the Burn Unit, allocated into Group A those with factor XIII assessment (n = 20), and Group B, those without assessment (n = 20). Erythrocyte transfusion was guided by a hemoglobin trigger of 10 g.dL-1 and the other blood products by routine coagulation and ROTEM® tests. Analysis of blood product consumption included units of erythrocytes, fresh frozen plasma, platelets, and fibrinogen. The coagulation biomarker analysis compared the pre- and post-operative values. Results and conclusions: Group A (with factor XIII study) and Group B had identical total body surface area burned. All patients in Group A had a preoperative factor XIII deficiency, whose correction significantly reduced units of erythrocyte concentrate transfusion (1.95 vs. 4.05, p = 0.001). Pre- and post-operative coagulation biomarkers were similar between groups, revealing that routine coagulation tests did not identify factor XIII deficiency. There were no recorded thromboembolic events. Correction of factor XIII deficiency in burn surgery proved to be safe and effective for reducing perioperative transfusion of erythrocyte units.